Protein markers for discrimination of meat species in raw beef, pork and poultry and their mixtures. (15th February 2017) - Kim, Gap-Don; Seo, Jin-Kyu; Yum, Hyeon-Woong; Jeong, Jin-Yeon; Yang, Han-Sul
Highlights: A few proteins showed different electrophoretic mobility among meat species. LC-MS/MS analysis allows the identification of species regardless of the same protein. Meat species could be identified from fresh meat and their mixtures by 1D gel electrophoresis. Commonly distributed proteins can be markers for discrimination of meat species. Abstract: The purpose of this study was to find discrimination markers for four major meat species such as beef, pork, chicken and duck. Myofibrillar and sarcoplasmic proteins isolated from each meat type were analyzed by one-dimensional gel electrophoresis and some proteins were identified through LC-MS/MS analysis. We confirmed that troponin I (TnI), enolase 3, l -lactate dehydrogenase (LDH) and triose-phosphate isomerase (TPI) could be useful markers for discrimination of mammals from poultry due to their different electrophoretic mobility. Tropomyosin 1 and carbonic anhydrase 3 were observed as muscle fiber type-related proteins and these could also be markers to distinguish mammals from poultry. Species-specific peptides identified by LC-MS/MS spectra allow the identification of each species regardless of the same protein. Therefore, it is easy to discriminate between mammals and poultry by comparing the electrophoretic mobility of TnI, enolase 3, LDH, TPI and CA3, and each species could be identified through LC-MS/MS analysis.